Aid-Financed Public Investments and the Dutch Disease: Evidence from Tanzania - Emmanuel E. Asmah; Jörgen Levin (Örebro University School of Business, 2008)
In this paper we discuss the impact of scaling-up aid in Tanzania using an economy-wide dynamic CGE model. The major conclusions coming out from this work is that productivity effects matter. If additional aid and consequently increased public spending has a positive impact on productivity this would spur GDP growth and reduce the risk of an appreciating real exchange rate. In a way this resembles previous results in the aid-growth literature that aid has a positive impact on growth in a country with good economic policies assuming that good policies have a positive impact on productivity. Presenting various scenarios on the impact of additional aid a sustained GDP growth rate of around 7 percent would be possible to achieve in a modest scaling-up aid scenario without any significant changes in the real exchange rate.
Keywords: F35; O11; O55; 330; Aid:Dutch:Disease:Tanzania